The Use of Euphemism on the Talk Show â€œSeteru Luhut vs Harisâ€ - Hasibuan, Alika Sandra; Tausya, Resi Syahrani; Sinaga, Lusiana (TALENTA Publisher, 2023)
This study aims to describe the use of the types and meanings of any euphemisms contained in Najwa Shihab's talk show entitled